O33 Earlier cancer diagnosis after myositis onset is associated with improved long term survival: results from UK, French and Czech cohorts. (20th April 2020) - Oldroyd, Alexander; New, Paul; Lamb, Janine; Ollier, William; Cooper, Robert; Mariampillai, Kuberaka; Benveniste, Olivier; Vencovský, Jiří; Mann, Heřman; Chinoy, Hector
Abstract: Background: The idiopathic inflammatory myopathies (IIMs) are associated with cancer. Cancer screening is advocated in new IIM cases; however no study has investigated if this confers improved long-term survival. This study aimed to investigate if a shorter time between IIM onset and cancer diagnosis is associated with improved survival. Methods: Verified adult-onset IIM (dermatomyositis, polymyositis, anti-synthetase syndrome) cases, according to the International Myositis Classification Criteria, were recruited from three separate UK (UKMYONET), France and Czech-based cohort studies. Only cases with cancer diagnosis following IIM onset were included in analysis. The time between IIM onset and cancer diagnosis was calculated for each case. The relationship between survival at the end of follow up and time between IIM onset and cancer diagnosis was quantified via calculation of hazard ratios using a Cox-proportional hazard model, adjusted for age and gender. Results: A total of 193 (66% female) IIM cases with a total of 1, 395 person-years follow up were included in the analysis (Table 1 ). Data of 120 UK, 45 Czech and 28 French participants were analysed. Breast was the most common site of cancer (16%), followed by lung (9%) and bowel (6%). Forty six (24%) deaths occurred within the follow up period. The IIM onset to cancer diagnosis time was shorter for those that survived at the end of follow up, compared to those that died: 4.6 years (IQR 1.2, 10.7), vs 5.8 years (IQR 1.6, 13.8), respectively. Cox-proportional hazard modelling, indicated that a longer time between IIM onset and cancer diagnosis was significantly associated with death (HR 1.06 [95% CI 1.02, 1.10]). This significant relationship was only demonstrated in the female cohort when analysed separately: female HR 1.06 (95% CI 1.01, 1.10), male HR 1.08 (95% CI 0.98, 1.18). Conclusion: Using data from three international cohorts, this study has, for the first time, identified that earlier cancer diagnosis after IIM onset is associated with improved long term survival. This finding was observed in the female cohort only. This study therefore indicate that cancer screening in newly diagnosed IIM cases without a preceding cancer history should be carried out, especially in female cases. Disclosures: A. Oldroyd None. P. New None. J. Lamb None. W. Ollier None. R. Cooper None. K. Mariampillai None. O. Benveniste None. J. Vencovský None. H. Mann None. H. Chinoy None.